Acoustic wavelength effects on the propagation of SAW on piezo-crystal and polymer substrates - Malik, A.F. (2013)
The design, fabrication and characterization of Surface Acoustic Wave (SAW) delay lines on piezo-crystalline and polymer substrate is outlined in this paper. The SAW delay lines consist of two sets of Inter-Digital Transducers (IDT) separated by a certain distance on the surface of the piezoelectric substrate. Initially, the design parameters of the SAW delay lines are obtained using Impulse Response model. Then, the device is fabricated using conventional lithography process. The transmission coefficients (S21) of the SAW devices fabricated on 500 Î¼m-thick Lithium Niobate (LiNbO3) and on 110 Î¼m-thick polyvinyldeneflouride (PVDF) substrates are then observed using vector network analyzer. It is found that SAW devices designed to operate at 55-196 MHz on LiNbO3 has S21 with losses within 10-20 dB. On the other hand, SAW devices designed to operate on PVDF, do not show any credible signal. The successful transmission of SAW on LiNbO3 shows that appropriate design, fabrication and characterization methodology has been adopted. Unfortunately, due to the thin PVDF layer, the acoustic signal transverse downward beyond the thickness of the PVDF rendering the SAW devices non-operational. From the data collected, it is therefore believed that successful generation of SAW on piezo-crystal and polymer substrate could only be realized if the thickness of the PVDF is at least six times the acoustic wavelength of the SAW itself. Â© 2013 IEEE.